Examples of unusual construction scaffoldings used for renovation works of historic buildings = Przykłady realizacji nietypowych rusztowań budowlanych wykorzystywanych do prac renowacyjnych obiektów zabytkowych - Robak, Aleksander; Pieńko, Michał; Błazik-Borowa, Ewa (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
A few examples of scaffoldings designed, built and used in recent years in Poland have been presented here in this paper. There have been described facilities of various forms, which are surrounded by scaffoldings. This makes the design and assembly processes demand large labour input. The main focus has been set to the problems in the operation of scaffoldings used during the renovation of historic monuments.
Keywords: rusztowania; obliczenia statyczne; schemat statyczny; scaffolding; static analysis; static scheme